Association between disability status and dental attendance in Australia—A population‐based study. Issue 1 (6th September 2020) - Lopez Silva, Claudia Patricia; Singh, Ankur; Calache, Hanny; Derbi, Hajer A.; Borromeo, Gelsomina L.
Abstract: Aims: Disability is a key social determinant of health. The objective of this study was to test the association between disability status and irregular dental attendance among the Australian population, and to examine whether the observed association varied among adolescents. Methods: Data on 17 501 participants from The Household, Income and Labour Dynamics in Australia (HILDA) were analysed. The main outcome examined was irregular dental attendance (two or more years since last dental visit) with disability as the primary exposure. Multivariable logistic regression models were fitted to test the associations between disability and dental attendance pattern. Models were adjusted for age, gender, country of birth, region of residence, education and income. Analysis was repeated among adolescents (15‐ to 24‐year‐old) to examine for variations in observed association. Results: One in four participants reported having a disability. Unadjusted model showed that the odds for irregular dental attendance were 1.40 times greater (95%; CI, 1.30‐1.51) in those with disability than those without disability. After adjusting for all covariates, participants with disability had 1.20 times higher odds (95%; CI 1.10‐1.30) of irregular dental attendance than those without disability. Irregular dental attendance was 1.41 times greater (95%; CI 1.10‐1.80) in those with disability aged 15‐24 years than those without disability. Conclusions: Australian individuals with disability are more likely to have irregular dental attendance than those without.